Meshing Theory of Circular Arc Profile Spiral Bevel Gear based on Form Method Machining - He Zhiwei Duan Jianzhong (Jixie chuandong)
The application of numerical control forming method machining in circular arc profile bevel gear is discussed, it is proved that the circular arc profile spiral bevel gear based on this method conforms to the basic law of tooth profile meshing, and the principle of determining the guiding line (the line of the tooth profile along the conical surface of the joint) is given. This work provides technical support for efficient machining of circular arc profile spiral bevel gear.